DIGITALISASI EKONOMI SYARIAH DI KALANGAN KAUM MILENIAL UNTUK PENGEMBANGAN EKONOMI SYARIAH - Ratu Surya Atmajaya; Misbakhul Munir Mubarok (Jurnal Inovasi Penelitian, 2022)
The millennial generation is a group that is very synonymous with digital technology. Millennials rely a lot on digital communication tools in their daily lives. So that digital technology is no longer just a contemporary style but has become a necessity for various activities. This research was conducted in order to find out the extent of the potential of millennials for sharia economic development. The research method uses a literative qualitative method that explains the behavior of Indonesian millennials in digital technology and the potential potential that can be utilized for the development of the Islamic economy. The analysis technique carried out in this case is by examining various literatures, presenting good data through the results of researchers' observations of the millennial phenomenon, then proceeding with drawing conclusions. The results obtained from this study are first, the life behavior of Indonesian millennials is strongly influenced by digital technology. Second, there is a need for massive breakthroughs in socialization, information, and other efforts to introduce Islamic economics among millennials by using digital technology.